SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP MENGGUNAKAN LOGIKA FUZZY (STUDI KASUS DI MASCOM SUKOHARJO) - Jatmiko, Aditya Dwi; Anwariningsih, Sri Huning; Susilo, Dahlan (Gaung Informatika, 2015)
Mascom  computer  store  is  one  of  the  stores  that  serve  to  sale  and  purchase  of computers.  The process  in  selling  notebook, process  there is a problem in the  service to the customer.  The  officer  find  difficulty  in  selling  notebook to work  customer questions that are ambiguous.  Of the handle the problem in answering customer questions  uses fuzzy logic. The uses  fuzzy  logic  based  on,  the  concept  of  fuzzy  logic,  is  easy  to  understand  ,  very  flexible logic  ,  on  has  the  tolerance  of  unpropriate  among  other.  In  this  final  project  development system of waterfall method un structure based design is used. Decision support system was made by using Visual Basic 6. This decision support system helps in notebook selling that are ambigious  becomes  easier  to  understand  for  the  customer.  This  result  of  final  project  is application that can be used by Mascom in decesing notebook for customer.Keyword: